2022
DOI: 10.1016/j.jds.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of 3D printed nano-porous hydroxyapatite bone graft for alveolar ridge preservation: A randomized controlled trial

Abstract: Background/purpose Ridge resorption after tooth extraction may result in inadequate bone volume and unfavorable ridge architecture for ideal implant placement. The use of bone substitutes has been advocated to fill extraction sites and to enhance primary implant stability. This study was made to evaluate the clinical efficacy of novel 3D printed nano-porous hydroxyapatite (3DP HA, test group) in comparison to nano-crystalline bone graft (NanoBone®, control group) in alveolar ridge preservation pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The second layer of the 3DHA block graft, which is composed of xenogenic bone graft, may also slow down the resorption of 3DHA. It could also increase the volume of the graft area [17,51]. These findings agree with the hypothesis that xenografts added to autogenous block grafts lead to less resorption compared with autogenous block grafts alone [55].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The second layer of the 3DHA block graft, which is composed of xenogenic bone graft, may also slow down the resorption of 3DHA. It could also increase the volume of the graft area [17,51]. These findings agree with the hypothesis that xenografts added to autogenous block grafts lead to less resorption compared with autogenous block grafts alone [55].…”
Section: Discussionsupporting
confidence: 87%
“…At higher magnification, newly formed bone was observed around the graft particles and blood vessels. Histomorphometric analysis revealed that the percentages of bone tissue, new bone formation, residual graft, and connective tissue were similar to the results from our previous study [51]. At six months, 3DHA remained at the recipient site and was completely integrated into the graft site, which suggests that it could be a space maintainer and ideal material for alveolar bone augmentation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Micro-CT analysis after 4 and 12 weeks of implantation indicated that the implant significantly stimulated new bone production (Figure f). Borvornwu et al verified the restoration effect of additively manufactured nano-HA in alveolar bone, where implants were filled with the new bone around both the root tip and crown after implantation and showed significant degradation and resorption after some time. The additive manufacturing technologies of HA are diverse and comparatively sophisticated.…”
Section: Advances In Additive Manufacturing Of Bioceramic Implantsmentioning
confidence: 98%
“…Encouragingly, several combinations of bioceramic and 3D printing technologies appear promising for clinical use, particularly 3D-printed TCP and HA scaffolds that have been successfully tested in humans, suggesting that biodegradable bioceramic scaffolds can be used as reliable bone graft materials to facilitate the bone repair and bone remodeling. 206,209 Researchers have demonstrated a digital approach for creating customized clinical-scale CP scaffolds that can be transplanted into alveolar bone defects using 3D imaging, design, and printing. In addition, a strong foundation for future studies to evaluate personalized medical approaches to treat alveolar bone defects was established.…”
Section: Oral and Maxillofacial Surgerymentioning
confidence: 99%